Accuracy of intravenous and enteral preparations involving small volumes for paediatric use: a review. Issue 2 (4th January 2017) - Ainscough, L P; Ford, J L; Morecroft, C W; Peak, M; Turner, M A; Nunn, A J; Roberts, M
Abstract : Background: Children often need to be administered very small volumes of medicines that are authorised for use in adults. Neonatal drug delivery is particularly challenging, and doses are often immeasurable with the equipment currently available. Aim: To summarise research to date on the accuracy of intravenous and enteral medicine preparation requiring small volumes (<0.1 mL), with a focus on paediatric use and to identify areas for further work. Method: Twenty-three publications were identified for the narrative review via: Web of Science (1950–2016), Cumulative Index to Nursing and Allied Health Literature (1976–2016), Excerpta Medica Database (1974–2016) and International Pharmaceutical Abstracts (1970–2016) searches. Nine additional papers were identified through backward citation tracking and a further 17 were included from the personal knowledge of the review team. Results: Measurement of volumes (<0.1 mL), for enteral and intravenous dosing, accounts for 25% of medicine manipulations within paediatric hospitals. Inaccuracies are described throughout the literature with dose administration errors attributed to technique, calculation, dilution and problems associated with equipment. While standardised concentrations for intravenous infusion and drug concentrations that avoid measurement of small volumes would ameliorate problems, further work is needed to establish accurate methods for handling small volumes during the administration of medicines to children and risk minimisation strategies to support staff involved are also necessary. Conclusions: This review has revealed a paucity of information on the clinical outcomes from problems in measuring small volumes for children and highlighted the need for further work to eliminate this source of inaccurate dosing and potential for medication error.